(untitled) (Journal of Psychiatrists’ Association of Nepal, 2014)
Background There are many definition of liaison psychiatry. The American Academy of psychosomatic medicine has suggested the term “medical and surgical psychiatry”. Much of the literature on Consultation Liaison (C-L) Psychiatry concerns the psychiatric assessment and management of patients in a general hospital. Method This was a descriptive study consisting of all the cases referred for liaison psychiatric consultation from inpatient units of various departments of Tribhuvan University Teaching Hospital, between October 2012 to April 2013. Patients of any age and of either gender were included. Result A total of 95 patients were referred from different departments of the hospital for liaison psychiatric consultation within the 6 months period. Majority of the subjects were male .The mean age of the subjects was 42.47 years (±19.98). Neurotic and stress-related disorders were seen associated with female. Conclusion: Mainly young adults and adult between 21-50 years of age are referred for liaison. Neurotic and stress-related disorders (30.5%), organic mental disorders (27.4%) and mental and behavioral disorders due to substance use cases (16.8%) were mainly referred for liaison psychiatric consultation. DOI: http://dx.doi.org/10.3126/jpan.v2i2.9721 J Psychiatrists’ Association of Nepal Vol.2, No.2, 2013 22-25